New Fisheries-related data from the Mediterranean Sea (April 2015) - P.K. KARACHLE; A. BAŞUSTA; N. BAŞUSTA; D. BOSTANCI; K. BUZ; H. GIRGIN; I. CHATER; L. KOKOKIRIS; S. KONTAŞ; M.-H. KTARI; C.D. MARAVELIAS; G. MINOS; et al. (Mediterranean Marine Science, 2015)
In this second Collective Article with fisheries-related data from the Mediterranean Sea we present the evaluation of bony structures in aging of Barbus tauricus, otolith dimensions-body length relationships for two species (Trachinus draco and Synchiropus phaeton), information on the growth of juvenile Thunnus thynnus and of Ruvettus pretiosus, weight-length relationships for three species (Aulopus fiamentosus, Thunnus thynnus and Tylosurus acus imperialis) and data on feeding habits and reproduction of Aulopus fiamentosus.